PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS LITERASI SAINS PADA MATERI SISTEM RESPIRASI KELAS XI SMA - Khasanah, Nurul Uswatun; Arnentis, Arnentis; Sayuti, Irda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce a scientific literacy-based Student Worksheet on quality material for the Class XI High School Respiration System. This research was conducted at the Faculty of Teacher Training and Education, University of Riau, SMAN 1 Pekanbaru and SMAN 8 Pekanbaru in October-February 2021. The type of research used was Research and Development (R&D) with the ADDIE research model consisting of 5 stages, namely analysis, design, development, implementation and evaluation. In this study, researchers only reached the development stage. The data collection instruments were in the form of validation sheets and respondent questionnaires. The results of the validation of the Student Worksheet based on scientific literacy on the Respiration System material for class XI SMA are at an average value of 3.75 with a very valid category. The result of the limited trial score I was 3.60 with a very good category. The result of the limited trial score II was 3.69 with a very good category. Thus, the scientific literacy-based Student Worksheet on the Respiration System material for class XI SMA has been successfully developed with very good quality and can be implemented on a wider scale. Key Words: Student Worksheet, Science Literacy, Respiratory System